2003
DOI: 10.1001/archneur.60.2.268
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Clinical and Magnetic Resonance Imaging Findings in a Family With Proteolipid Protein Gene Mutation

Abstract: The unusual genetic, magnetic resonance imaging, and clinical findings of this family confirm the wide variability of PLP-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Other genetic disorders with X‐linked inheritance, like fragile X, FG, Opitz syndromes and some disorders of cortical development, which can be symptomatic in carrier mothers, were soon excluded on clinical grounds, laboratory investigation and brain neuroimaging. X‐linked PLP gene was tested in patient 1 because of pyramidal signs and slight white matter abnormalities [Battini et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Other genetic disorders with X‐linked inheritance, like fragile X, FG, Opitz syndromes and some disorders of cortical development, which can be symptomatic in carrier mothers, were soon excluded on clinical grounds, laboratory investigation and brain neuroimaging. X‐linked PLP gene was tested in patient 1 because of pyramidal signs and slight white matter abnormalities [Battini et al, 2003].…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients with SPG2, as well as clinically asymptomatic obligate carrier mothers of males with classical Pelizaeus-Merzbacher disease, have been described with non-specific periventricular and subependymal white matter changes on MRI, and cystic changes in the basal ganglia (Fig. 2J and K;Battini et al, 2003;Warshawsky et al, 2005;Hurst et al, 2006). A young female presenting with subacute gait disturbance and periventricular white matter lesions was recently described with biallelic pathogenic mutations in SPG11 ( Fig.…”
Section: Hereditary Spastic Paraplegiasmentioning
confidence: 99%
“…223,224 A high prevalence of WMHs is also found in 22q11-deletion syndrome frequently associated with psychosis, 225 cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, which is caused by mutations in the NOTCH3 gene on chromosome 19 and frequently associated with depression, and other less common genetic conditions. [226][227][228][229] Nongenetic factors are associated with WMHs as well; [230][231][232][233][234][235][236][237][238] for example, Moore et al 239 reported a correlation between WMH and season of birth in a group of patients with BD. Thus, it appears that WMHs are not specific to BD and their usefulness as an endophenotype remains to be established.…”
Section: Basal Gangliamentioning
confidence: 99%